Strategi Peningkatan Pembiayaan Bagi Hasil Pada Bank Syariah di Indonesia - Rusandry Rusandry (Jurnal Ilmiah Wahana Pendidikan, 2021)
This research identified the growth of financing activities in Islamic banks in Indonesia within the period of 2005-2016 and 2010-2016 to discover the need of Islamic banks to increase the volume of financing. This study proposed the internal variables; CAR, ROA, ROE, NPF, and BOPO, and the external variables; inflation, BI rate, exchange rate, and GDP. The data consisted of 11 Bank Umum Syariah (Islamic commercial bank) listed in Bank Indonesia. The macroeconomic factors included the inflation rate, BI rate, exchange rate, and the GDP in March 2005 to December 2016. All the data are processed using panel regression. This study found that: (1) Financial ratio; CAR, ROA, ROE, NPF, and BOPO do not influence the financing in three Islamic banks, and only ROE that statistically significant to have impact on financing to the other eight Islamic banks. (2) Macroeconomic indicators; Inflation, BI rate, exchange rate, and GDP are not statistically significant to affect the three Islamic banks. The result identified that only GDP that affect the financing in eight Islamic banks. (3) Regression output show that the ROE and GDP are statistically significant with positive relation to influence the financing activities in Islamic banks.